'Now I'm just like anyone else in the community': Work, Welfare, and Community Expectations of Refugees in Australia. (3rd December 2020) - Boese, Martina; Van Kooy, John; Bowman, Dina
Abstract: This article analyses policy documents and data from interviews with employment and settlement service providers, employers, and government officials to explore the increasing shift of Australian refugee settlement policies towards neoliberal imperatives of productivity and self-sufficiency. The responses of service providers shed light on prevalent constructions of refugee subjecthood and related expectations of humanitarian entrants as potential labour market participants. Our analysis highlights the policy rationales that underpin the contemporary design and delivery of refugee settlement support, and draws attention to variations in service providers' adoption of these rationales. We argue that, while the realignment of refugee settlement support in Australia towards 'workfare' is consistent with emergent global narratives of 'enhancing refugee self-reliance', the significance of this shift lies in the ideologically driven erosion of the primary protective purpose of Australia's long-standing humanitarian migration programme.